Control of core argon impurity profile by ECH in KSTAR L-mode plasmas. (6th May 2015) - Hong, Joohwan; Hun Lee, Seung; Kim, Juhyung; Seon, C.R.; Lee, S.G.; Park, G.Y.; Lee, K.D.; Henderson, S.S.; Lee, H.Y.; Sun Park, Jae; Jang, Juhyeok; Jang, Siwon; et al.
Abstract: Experiments on trace argon impurity transport in L-mode discharges were performed on Korea superconducting tokamak advanced research (KSTAR) with electron cyclotron resonance heating (ECH). Ar emission was measured by soft x-ray (SXR) arrays and vacuum UV (VUV) diagnostics. A significant reduction in the core Ar emissivity was observed with core ECH. The reduction was the largest with on-axis heating and became smaller with outward heating positions. The diffusivity and convection velocity of Ar were obtained by analysis of the SXR data with the SANCO impurity transport code for the on-axis ECH and the non-ECH shots. In the on-axis ECH case, both diffusivity and convection velocity increased. Furthermore, the convection changed its direction from inward to outward in the plasma core ( r / a < 0.3), resulting in a hollow profile of the total Ar density. Together with the reduction in the SXR signals, the hollow impurity profile in the core and the reversal of the convection velocity consistently confirm that ECH can reduce impurity accumulation in the core region. Neoclassical impurity transport and linear stability of micro-turbulence were calculated and discussed in relation to the possible transport mechanism.